Characterization of Reproductive Dormancy in Male Drosophila melanogaster - Kubrak, Olga I.; Kučerová, Lucie; Theopold, Ulrich; Nylin, Sören; Nässel, Dick R. (Frontiers in Physiology, 2016)
Insects are known to respond to seasonal and adverse environmental changes by entering dormancy, also known as diapause. In some insect species, including Drosophila melanogaster, dormancy occurs in the adult organism and postpones reproduction. This adult dormancy has been studied in female flies where it is characterized by arrested development of ovaries, altered nutrient stores, lowered metabolism, increased stress and immune resistance and drastically extended lifespan. Male dormancy, however, has not been investigated in D. melanogaster, and its physiology is poorly known in most insects. Here we show that unmated 3-6 h old male flies placed at low temperature (11°C) and short photoperiod (10 Light:14 Dark) enter a state of dormancy with arrested spermatogenesis and development of testes and male accessory glands. Over three weeks of dormancy we see a dynamic increase in stored carbohydrates and an initial increase and then a decrease in lipids. We also note an up-regulated expression of genes involved in metabolism, stress responses and innate immunity. Interestingly, we found that male flies that entered reproductive dormancy do not attempt to mate females kept under non-diapause conditions (25°C, 12L:12D), and conversely non-dormant males do not mate females in dormancy. In summary, our study shows that male D. melanogaster can enter reproductive dormancy. However, our data suggest that dormant male flies deplete stored nutrients faster than females, studied earlier, and that males take longer to recover reproductive capacity after reintroduction to non-diapause conditions.